Effect of reading an educational booklet about sickle cell disease on family members' knowledge - Sarah Vieira Figueiredo; Thereza Maria Magalhães Moreira; Daniella Barbosa Campos; Edna Maria Camelo Chaves; Ilvana Lima Verde Gomes (Universidade Federal do Ceará, 2021)
Objective: to analyze the effect of reading an educational booklet about sickle cell disease related to family members' knowledge. Methods: quasi-experimental study, with 20 children´s family members with sickle cell disease. A form was used before and 30 days after medical consultation (pre- and post-test). The booklet was given to the family member on the day of the consultation. Analysis was performed using Statistical Package for the Social Science version 20 with the Shapiro-Wilk, Student's t, McNemar's chi-square and Odds Ratio statistical tests. Results: all participants were female, mostly mothers aged 20 to 30 years with high school education. The analysis revealed increase in the number of correct answers after reading the booklet with statistical significance (p<0.001). Conclusion: the reading of the booklet and the strategies used to encourage it contributed to increase the knowledge of family members about some disease aspects, enabling them to better deal with this disease.